Theoretical and Experimental Studies for Inhibition Potentials of Imidazolidine 4-One and Oxazolidine 5-One Derivatives for the Corrosion of Carbon Steel in Sea Water - Kubba, Rehab M; Al-Joborry, Nada M.; Al-lami, Naeemah J. (Iraqi Journal of Science, 2020)
Two derivatives of Iimidazolidin 4-one (IMID4) and Oxazolidin 5-one (OXAZ5), were investigated as corrosion inhibitors of corrosion carbon steel in sea water by employing the theoretical and experimental methods. The results revealed that they inhibit the corrosion process and their %IE followed the order: IMID4 (89.093%) > OXAZ5 (80.179%). The %IE obtained via theoretical and experimental methods were in a good agreement with each other. The thermodynamic parameters obtained by potentiometric polarization measurements have supported a physical adsorption mechanism which followed Langmuir adsorption isotherm. Quantum mechanical method of Density Functional Theory (DFT) of B3LYP with a level of 6-311++G (2d, 2p) were used to calculate the geometrical structure, physical properties and inhibition efficiency parameters, in vacuum and two solvents (DMSO and H2O), all calculated at the equilibrium geometry, and correlated with the experimental %IE. The local reactivity has been studied through Mulliken charges population analysis. The morphology of the surface changes of carbon steel were studied using SEM and AFM techniques.